A flexible device for ocular iontophoretic drug delivery - Zhang, Yushi (Biomicrofluidics, 2016)
In this work, a flexible ocular iontophoretic device, which can be fabricated by batch processing, is reported. In vivo experiments were conducted on rabbit eyes, and the results demonstrated this device could realize ocular iontophoresis effectively, simply, and conveniently. Compared to conventional eye cups, it can be placed under the eyelid and can deliver ions through a small area on the eyeball, reducing tissue damage caused by the drug during ion penetration. Owing to the flexibility of the device, the device can be easily seated under the eyelid stably during iontophoresis. Manganese ions as a tracer for detection of optic nerve damage were delivered into rabbit eyes by this iontophoretic device. Under 1 mA for 600 s, the average Mn(2+) concentration in the eye ball after iontophoresis was 102 ng/ml, while the one in the control group was 23 ng/ml. Using 2 mA for 600 s, the average concentration was 271 ng/ml, while it was 38 ng/ml in the control group. Thermal injury during iontophoresis was not observed under an applied current of no more than 2 mA for no longer than 10 min, with the local temperature less than 38 °C, measured by an infrared thermal imager.